Author Correction: Plumbagin attenuates cancer cell growth and osteoclast formation in the bone microenvironment of mice - Yan Wei; Wang Ting-yu; Fan Qi-ming; Du Lin; Xu Jia-ke; Zhai Zan-jing; Li Hao-wei; Tang Ting-ting (Acta Pharmacologica Sinica, 2020)
During re-read of our previous article Plumbagin attenuates cancer cell growth and osteoclast formation in the bone microenvironment of mice published in Acta Pharmacologica Sinica, we were regretted to point out a mistake shown in Fig. 2a. The representative ﬁgure chosen to indicate the inhibitory effect of 4 mg/kg of plumbagin treatment at 1 week against MDA-MB-231SArfp cells localization within bone environment was incorrect due to the mishandling in manuscript preparation. Although this correction does not affect the results and conclusion of the paper, all the authors agree on the correction of our negligence as providing the corrected Fig. 2a presented below. We feel sorry and apologize for all the inconvenience it caused.